Cinema Activities in Social Work: The Film Forum as an Educational Innovation Experience - Navajas-Pertegás, Nina; Pérez-Cosín, José-Vicente (Cuadernos de Trabajo Social, 2023)
Our society is dominated by audiovisual media. However, our education system does little to  train students in audiovisual language. From the perspective of the UN Sustainable Development Goals, film forums stand out as a pedagogical strategy that promotes the cognitive, communicative and socioemotional dimensions of learning. This paper analyses a teaching experience involving a film forum and social policy with 42 undergraduate students at a Spanish university. The aim was to explore whether students considered that the  forum fostered interest, participation, meaningful learning and a critical view. The data were collected through a questionnaire. Most students rated the educational innovation experience positively because: (a) they learned by connecting the content of the films shown with the theory of the subject; (b) the activity encouraged a reflective and critical spirit when analysing social issues from a gender and human rights perspective. The conclusion was that film forums have a positive impact on learning when designed and used with a clear purpose.
Keywords: Film Forum and Meaningful Learning; Film Forum and SDG; Social Work Educational Innovation; University Teaching